Hemocytes and fat body cells, the only professional immune cell types in Drosophila, show strikingly different responses to systemic infections - Vaibhvi, Vaibhvi; Künzel, Sven; Roeder, Thomas (Frontiers in Immunology, 2022)
The fruit fly Drosophila is an excellent model to study the response of different immunocompetent organs during systemic infection. In the present study, we intended to test the hypothesis that the only professional immune organs of the fly, the fat body and hemocytes, show substantial similarities in their responses to systemic infection. However, comprehensive transcriptome analysis of isolated organs revealed highly divergent transcript signatures, with the few commonly regulated genes encoding mainly classical immune effectors from the antimicrobial peptide family. The fat body and the hemocytes each have specific reactions that are not present in the other organ. Fat body-specific responses comprised those enabling an improved peptide synthesis and export. This reaction is accompanied by transcriptomic shifts enabling the use of the energy resources of the fat body more efficiently. Hemocytes, on the other hand, showed enhanced signatures related to phagocytosis. Comparing immune-induced signatures of both cell types with those of whole-body responses showed only a minimal correspondence, mostly restricted again to antimicrobial peptide genes. In summary, the two major immunocompetent cell types of Drosophila show highly specific responses to infection, which are closely linked to the primary function of the respective organ in the landscape of the systemic immune response.